How the ELE projects aims to bring the voices of the Wikimedia communities on Digital Language Equality into future European Commission Programs - Heuschkel, Maria Heuschkel (Septentrio Conference Series, 2021)
The European Commission is funding the project “European Language Equality” and next to 52 other partners, Wikimedia Deutschland is part of this partner consortium. The project is aiming to address the challenge that not all 24 official EU languages or the regional and minority languages in Europe have the same digital support. In order to achieve a state in which all languages have the technological support necessary for them to continue to exist and prosper in the digital age, the project partners are preparing a convincing agenda and roadmap on how to get there by 2030. The Wikimedia movement, consisting of volunteers and organizations whose daily business is dealing with languages and language technology, is a major stakeholder for the language technology community. In order to know what it will take to get to a state of full digital equality we want the project consortium to know the pains, challenges, wishes and needs of the volunteers and communities keeping the multi-language environment of Europe alive everyday. This lightning talk will give a short introduction to this European project and present a survey that is used to collect needs, hopes and challenges from the language technology community. We are hoping that with this the communities perspective on digital language equality will influence future programs, projects, funding and structures on an European level.